(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Propolis from stingless bees (Heterotrigona itama) is a resinous compound that exhibits antihyperglycaemia, free radical scavenging, and cardioprotective properties. The effect of propolis on diabetic vessels has not been investigated. Thus, this research aimed to determine the effect of propolis supplementation on the level of antioxidants and its mechanism of action in the aorta of diabetic rats. Male Sprague-Dawley rats were divided into five groups (n=8/group): healthy (control), untreated diabetes (DM), metformin-treated diabetes (DM+M, 300 mg/kg/day metformin), propolis-treated diabetes (DM+P, 300 mg/kg/day propolis extract) and diabetes with combined treatment (DM+M+P, dosage as former). Oral supplementation was conducted for four weeks immediately upon successful induction of diabetes by streptozotocin (60 mg/kg, intraperitoneal injection). At the end of the study, the rats were euthanised, and thoracic aorta was processed into tissue homogenates to determine the levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase-1 (GPx-1) and soluble receptor for advanced glycation end-products (sRAGE). Aorta segments were harvested to examinetheir relaxation response towards graded concentration of acetylcholine (Ach; 10-8–10-4) M following precontraction with phenylephrine (PE; 10-6 M). Vasorelaxation towards a cumulative dose of propolis (0.01–1.00%) using PE-precontracted healthy aorta (n=6/experiments) was investigated under various simulated conditions: physiological buffer, L-NAME (10-4 M), methylene blue (10-5 M), indomethacin (10-5 M) and elevated glucose (25 mM). Propolis maintained antioxidative enzymes and sRAGE decoy molecules in the aortic tissue of the diabetic rats. The amelioration of diabetes-induced impairment of endothelium-dependent relaxation by propolis was mediated through the nitric oxide(NO)–cyclic guanosine monophosphate (cGMP) pathway. This non-clinical study reports vasoprotective property of propolis in diabetes mellitus.